Macrophages—Key cells in the response to wear debris from joint replacements. Issue 10 (9th April 2013) - Nich, Christophe; Takakubo, Yuya; Pajarinen, Jukka; Ainola, Mari; Salem, Abdelhakim; Sillat, Tarvo; Rao, Allison J.; Raska, Milan; Tamaki, Yasunobu; Takagi, Michiaki; Konttinen, Yrjö T.; Goodman, Stuart B.; et al.
<x xml:space="preserve">Abstract</x> The generation of wear debris is an inevitable result of normal usage of joint replacements. Wear debris particles stimulate local and systemic biological reactions resulting in chronic inflammation, periprosthetic bone destruction, and eventually, implant loosening, and revision surgery. The latter may be indicated in up to 15% patients in the decade following the arthroplasty using conventional polyethylene. Macrophages play multiple roles in both inflammation and in maintaining tissue homeostasis. As sentinels of the innate immune system, they are central to the initiation of this inflammatory cascade, characterized by the release of proinflammatory and pro‐osteoclastic factors. Similar to the response to pathogens, wear particles elicit a macrophage response, based on the unique properties of the cells belonging to this lineage, including sensing, chemotaxis, phagocytosis, and adaptive stimulation. The biological processes involved are complex, redundant, both local and systemic, and highly adaptive. Cells of the monocyte/macrophage lineage are implicated in this phenomenon, ultimately resulting in differentiation and activation of bone resorbing osteoclasts. Simultaneously, other distinct macrophage populations inhibit inflammation and protect the bone‐implant interface from osteolysis. Here, the current knowledge about the physiology of monocyte/macrophage lineage cells is reviewed. In addition, the pattern and consequences of their interaction with wear debris and the recent developments in this field are presented. © 2013 Wiley Periodicals, Inc. J Biomed Mater Res Part A: 101A: 3033–3045, 2013.